URGENSI PENGEMBANGAN DESAIN TAROMPA DATUAK DALAM PENINGKATAN PEREKONOMIAN PERAJIN DAN KONSITENSI USAHANYA - Amrizal Amrizal; Sumadi Sumadi (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2019)
Tarompa Datuak is sociocultural footwear which is a cultural product inspired by a replica of “capal Rasul” brought by merchants from Arab and India. In accordance with the Minang proverb “sakali aie gadang sakali tapian barubah” (time change) in the socio-cultural context of tarompa which was originally shaped replica capal Rasul transforme by craftsmen in Malay land into “capal Malays” and in Ranah Minang called “tarompa datuak”, due to part of Datuak greatness clothes. As a craft product that is synonymous with Minang culture, it needs to be developed, in order to remain sustainable and sought by the wider community. The development of the design and the empowerment of craftsmen becomes imperative in the context of sociocultural change, because the potential of tarompa datuak can be transformed optimally into leather handicraft products that provide prosperity for the supporting community. For that, it is necessary to do this research with the aim of developing the design and ability of tarompa datuak crafters as well as improving the managerial system of his business, so that the potential of tarompa datuak handicraft is optimized and become a competitive handicraft amid the global cultural arena. The method used in this research refers to qualitative research methodology, namely participatory observation method is active observation. To make tarompa designs datuak, then conducted several stages of research, namely: a survey to the center of tarompa datuak craft; exploration; analysis and synthesis; designing by considering the factor of performance, function factor, marketing factor and consumer interest; and then transformed into a prototype tarompa datuak.